Gender inequalities in the response to combination antiretroviral therapy over time: the Swiss HIV Cohort Study1. Issue 5 (20th October 2014) - Rosin, C; Elzi, L; Thurnheer, C; Fehr, J; Cavassini, M; Calmy, A; Schmid, P; Bernasconi, E; Battegay, M
<x xml:space="preserve">Abstract</x> Objectives Gender‐specific data on the outcome of combination antiretroviral therapy (cART) are a subject of controversy. We aimed to compare treatment responses between genders in a setting of equal access to cART over a 14‐year period. Methods Analyses included treatment‐naïve participants in the Swiss HIV Cohort Study starting cART between 1998 and 2011 and were restricted to patients infected by heterosexual contacts or injecting drug use, excluding men who have sex with men. Results A total of 3925 patients (1984 men and 1941 women) were included in the analysis. Women were younger and had higher CD4 cell counts and lower HIV RNA at baseline than men. Women were less likely to achieve virological suppression < 50 HIV‐1 RNA copies/mL at 1 year (75.2% versus 78.1% of men; P = 0.029) and at 2 years (77.5% versus 81.1%, respectively; P = 0.008), whereas no difference between sexes was observed at 5 years (81.3% versus 80.5%, respectively; P = 0.635). The probability of virological suppression increased in both genders over time (test for trend, P < 0.001). The median increase in CD4 cell count at 1, 2 and 5 years was generally higher in women during the whole study period, but it gradually improved over time in both sexes (P < 0.001). Women also were more likely to switch or stop treatment during the first year of cART, and stops were only partly driven by pregnancy. In multivariate analysis, after adjustment for sociodemographic factors, HIV‐related factors, cART and calendar period, female gender was no longer associated with lower odds of virological suppression. Conclusions Gender inequalities in the response to cART are mainly explained by the different prevalence of socioeconomic characteristics in women compared with men.